Strategi Pengelolaan Sumber Daya Manusia dalam Mendorong Pertumbuhan Perusahaan: Studi Kasus pada Bangun Bang, Boedjang Group - Airiel; Yaroh, Dhela Lutfiyah; Salsabila, Mifta Fania; Yulinda (Sosiosaintika, 2025)
This study aims to fill this gap by examining the effectiveness of simple technology systems integrated with Standard Operating Procedures (SOPs) in the context of the regional property industry. This research employs a descriptive qualitative approach through an instrumental case study design based on the conceptual framework of Stake (1995). Located in Bangun Bang, a property business unit of the Boedjang Group in West Kalimantan, primary data were collected through semi-structured interviews with key informants from the HR department, triangulated with a review of internal policy documentation and indirect observation. The main findings reveal that Bangun Bang has been able to effectively manage workforce growth and business expansion through a very simple technological infrastructure (such as digital attendance and an employee intranet portal). The absence of a comprehensive HRIS is compensated by the implementation of a tiered "Card System" for discipline and strict SOP integration. Furthermore, a managerial innovation was discovered in the form of a promotion policy based not on past performance, but projected on future leadership potential assessments. The HR strategy at Bangun Bang demonstrates that medium-sized enterprises in developing regions can achieve competitive advantage without excessive technology investment, provided there is alignment between support systems, adherence to work culture, and a holistic talent management approach. The practice of promotion based on long-term potential challenges the traditional meritocracy paradigm and offers a mitigation model for the "Peter Principle".